Implementation of Household Waste Management Policy: A Siyasah Tanfidziyah Analysis of Local Government Regulation - Akbar Rizki Wahyu Pradana Madan Saputra; Eti Karini; Muhammad Jayus; Suraining Rosodor (Yayasan Pendidikan Islam Almatani, 2026)
This study examines the implementation of household and household-like waste management policies from the perspective of Siyasah Tanfidziyah, focusing on the exercise of governmental authority in policy execution. The research aims to analyze how local governments implement waste management regulations and to assess their alignment with Islamic principles of governance oriented toward public welfare (maslahah). This study employs field research with a qualitative descriptive approach. Primary data were obtained through interviews and documentation at the local Environmental Service, while secondary data were collected from relevant books, journals, and regulatory documents. Data were analyzed using descriptive analytical techniques. The findings indicate that the implementation of waste management policies remains suboptimal due to inadequate facilities and infrastructure, limited public education, and insufficient internalization of Islamic values related to environmental stewardship. These constraints hinder the effective realization of environmentally sustainable governance as envisioned in Siyasah Tanfidziyah. The study concludes that effective waste management requires the integration of regulatory enforcement with a religious-based approach that emphasizes public awareness and collective responsibility. Accordingly, this study recommends strengthening regulatory frameworks, enhancing Islamic-based environmental education, and promoting cross-sector collaboration at the community level to improve policy effectiveness